ANALYSIS OF ISLAMIC RELIGIOUS EDUCATION AND ETHICS TEXTBOOK FOR CLASS X HIGH SCHOOL - Fanani, Fuad Dikri; Istikomah (Academic Journal Research, 2024)
Teenage students, especially those in high school, are in the process of self-discovery. During this quest for identity, students may be susceptible to negative influences that deviate from Islamic teachings, potentially affecting their character. The challenge for students in their search for identity becomes even more pronounced in the rapidly evolving digital world, where they can access vast amounts of information to shape their self-concept. In this process, Islamic education and noble conduct serve as bridges to guide students in their self-discovery journey, enabling them to align their lives with the teachings of Allah Subhanahu Wa Ta'ala. The researcher conducted a study on the Islamic Education and Noble Conduct textbooks for 10th-grade students to assess whether the content in these textbooks can assist students in developing in line with Islamic values. The qualitative literature review method revealed that the Islamic Education and Noble Conduct textbooks for 10th-grade students already encompass Islamic moral values, serving as a foundation for students to shape their character and self-identity in a world filled with challenges.